Aluminum Activity in Alpine Tundra Soil, Rocky Mountain National Park, Colorado, U.S.A. Issue 8 (August 2016) - Evans, Andrew; Jacobs, Michael B.
Abstract : Abstract: Shifts in seasonal aluminum (Al) activity and speciation in poorly buffered alpine tundra soil, attributable to atmospheric deposition of reactive nitrogen, can result in increased Al bioavailability, adversely impacting high-altitude plant and microbial communities. To evaluate seasonal changes in Al soil solution chemistry, intact soil column leaching studies were conducted to determine pore water Al speciation and transport under saturated spring melt-off conditions and unsaturated late summer conditions. These results were compared with aqueous Al speciation in surface and groundwater seep samples collected during the June to August growing season. Analysis of soil column leachates, surface and groundwater seep samples, indicated that Al activity was controlled by the aluminum hydroxyl sulfate suite of minerals, jurbanite, basaluminite, and alunite. Soil pore water collected from saturated soil cores consisted primarily of aluminum fluoride (Al-F) complexes for pore volumes (PV) < 5.0, with aluminum hydroxyl (Al-OH) complexation increasing with continued elution. Leachates collected from unsaturated soil cores exhibited Al-F transport only within the soil wetting front, PV < 1.0, after which, Al-OH complexes were predominant. The presence of fluoride (F − ) in the soil pore water in the reactive solution front resulted in notable shifts between Al controlling solid phases and aqueous speciation. Similar shifts in Al speciation and controlling Al solid phases were observed in surface and groundwater seep samples, with sampling date and elevation. Results suggest that Al speciation and transport within alpine tundra soil may be seasonally influenced by soil moisture content and F − release from soil solid phases within the O/A1 soil horizons.